ASSESSMENT OF NUTRITIONAL STATUS, SELF-ESTEEM, AND QUALITY OF LIFE IN STOMATIZED PATIENTS - NAWAZ , A; RASOOL , F; ANWAR , M (Biological and Clinical Sciences Research Journal, 2023)
The prospective study of Nishtar Hospital Multan from January 2022 to January 2023 to assess the impact of intestinal stomas on patients' quality of life and nutritional status. Patients of both genders, aged > 18 years, having intestinal stoma, were included. A total of 100 participants were included in the study. A questionnaire including demographic details, information regarding the stoma, and the Rosenberg Self-Esteem Scale/UNIFESP-EPM quality of Life Scale was used to collect data.59 respondents had low self-esteem (<15), having a mean Score of 0.56; 11 had normal self-esteem with a mean value of 0.64, and 30 had high self-esteem (>25), having a mean of 0.62. A significant association and positive correlation existed between self-esteem and nutritional status (P= 0.04). Linear regression analysis showed a significant association between nutritional status and duration of stoma (P=0.011), type of stoma (P=0.05), monthly income (P=0.01), and number of meals/day (P=0.002). Moreover, there was a significant difference between median QoL – SeSi scores of urostomy patients (Mdn=18.5) compared to those who had a stoma (Mdn=16.5) or an inflamed appendix (16.0) (P= 0.04). Analysis of QoL-FF Score (relation with friends and family) showed urostomy patients (Mdn = 34.5) had substantially higher ratings than colostomy patients (median = 33.5, p = 0.02), and ileostomy patients (Mdn = 32.0, p = 0.025). There was no discernible difference between colostomy as well as ileostomy ratings. It was concluded that stoma patients' quality of life, self-esteem, and nutritional status are interconnected.